Armadillo is required for adherens junction assembly, cell polarity, and morphogenesis during Drosophila embryogenesis. - Cox, R.T.; Kirkpatrick, C.; Peifer, M. (Journal of Cell Biology, 1996)
Morphological and biochemical analyses have identified a set of proteins which together form a structure known as the adherens junction. Elegant experiments in tissue culture support the idea that adherens junctions play a key role in cell-cell adhesion and in organizing cells into epithelia. During normal embryonic development, cells quickly organize epithelia; these epithelial cells participate in many of the key morphogenetic movements of gastrulation. This prompted the hypothesis that adherens junctions ought to be critical for normal embryonic development. Drosophila Armadillo, the homologue of vertebrate beta-catenin, is a core component of the adherens junction protein complex and has been hypothesized to be essential for adherens junction function in vivo. We have used an intermediate mutant allele of armadillo, armadilloXP33, to test these hypotheses in Drosophila embryos. Adherens junctions cannot assemble in the absence of Armadillo, leading to dramatic defects in cell-cell adhesion. The epithelial cells of the embryo lose adhesion to each other, round up, and apparently become mesenchymal. Mutant cells also lose their normal cell polarity. These disruptions in the integrity of epithelia block the appropriate morphogenetic movements of gastrulation. These results provide the first demonstration of the effect of loss of adherens junctions on Drosophila embryonic development.